Determinants of Chronic Energy Deficiency among Pregnant Women in Stunting-Endemic Communities of South Sulawesi, Indonesia: A Cross-Sectional Study - Irma Irma; Sugirah Nour Rahman; Hasra Ryska; Jihan Fadhilah Arsyad (Fakultas Kesehatan Masyarakat Universitas Pancasakti, 2026)
Chronic Energy Deficiency (CED) among pregnant women remains a major public health problem because it increases the risk of adverse pregnancy outcomes and child stunting. Evidence on factors associated with CED in stunting-endemic areas is still limited. This study aimed to identify determinants of CED among pregnant women in stunting-endemic communities of Bone Regency, South Sulawesi, Indonesia. A community-based cross-sectional study was conducted among 209 pregnant women from 40 stunting-focus villages using a total sampling approach. CED was defined as a mid-upper arm circumference (MUAC) of <23.5 cm. Data were analyzed using Chi-square tests and multivariable logistic regression. The prevalence of CED was 29.7%. Factors significantly associated with CED were age of the last child (AOR=4.53; 95% CI: 1.46–14.38), ANC utilization (AOR=3.81; 95% CI: 2.69–5.66), pregnancy spacing (AOR=5.36; 95% CI: 2.53–11.37), household smoking history (AOR=4.63; 95% CI: 2.35–9.14), and family income (AOR=4.82; 95% CI: 2.31–9.53). Pregnancy spacing was the strongest determinant. CED remains common among pregnant women in stunting-endemic areas. Strengthening family planning, improving ANC utilization, promoting smoke-free households, and supporting low-income families are essential to improve maternal nutrition and support stunting prevention.